2007
DOI: 10.1016/j.schres.2007.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific familial risks of psychotic disorders and schizophrenia: A nation-wide epidemiological study from Sweden

Abstract: Objective-This study analyzed men and women separately by age at hospital diagnosis of psychotic disorder or schizophrenia and by maternal or paternal disease after taking several possible confounders into account. Methods-The MultigenerationRegister, in which all men and women born in Sweden from 1932 onwards are registered together with their parents, was linked to hospital data. This yielded 21,199 male and 19,029 female cases of psychotic disorders in addition to 12,799 paternal and 23,021 maternal cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“… The 4-parameter model was fitted to published datasets for (a) French male ulcerative colitis [ 18 ]; (b) schizophrenia [ 30 ]; (c) multiple sclerosis [ 31 ]; (d) ankylosing spondylitis [ 32 ]. Published data are shown as red dots and the computed curves as blue lines.…”
Section: Resultsmentioning
confidence: 99%
“… The 4-parameter model was fitted to published datasets for (a) French male ulcerative colitis [ 18 ]; (b) schizophrenia [ 30 ]; (c) multiple sclerosis [ 31 ]; (d) ankylosing spondylitis [ 32 ]. Published data are shown as red dots and the computed curves as blue lines.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported a positive association between a range of defects in the mitochondrial genome and the development of schizophrenia [ 387 , 388 ]. There is also a growing body of evidence suggesting an increased maternal transmission of schizophrenia, which may indirectly indicate a potential role for mitochondrial inheritance in the etiology of the illness [ 389 , 390 ]. Numerous authors have demonstrated an association between certain mitochondrial haplotypes and disease risk, and the associations also extend to age of onset[ 390 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results of twin, family, and molecular genetic studies strongly suggest that BPD [45, 46•] and psychotic disorders [47] are moderately to highly heritable.…”
Section: Association Between Maltreatment In Childhood and Psychotic mentioning
confidence: 99%